2005
DOI: 10.1152/jn.00915.2004
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Sleep and Wakefulness in the Thalamocortical System

Abstract: Hill, Sean and Giulio Tononi. Modeling sleep and wakefulness in the thalamocortical system. J Neurophysiol 93: 2005. First published November 10, 2004; doi:10.1152/jn.00915.2004. When the brain goes from wakefulness to sleep, cortical neurons begin to undergo slow oscillations in their membrane potential that are synchronized by thalamocortical circuits and reflected in EEG slow waves. To provide a self-consistent account of the transition from wakefulness to sleep and of the generation of sleep slow waves, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
376
2
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 361 publications
(396 citation statements)
references
References 148 publications
13
376
2
5
Order By: Relevance
“…The propagation speed in source space ranged from 0.4 to 6.3 m/s. The average speed was Ϸ2.2 m/s, was remarkably consistent across subjects (ranging from 2.0 to 2.3 m/s), and was roughly in agreement with previous estimations from EEG and computer simulations (9,23). Visual inspection of the streamlines for the spontaneous slow waves for each subject suggested the existence of a mesial slow wave highway oriented along the anterior-posterior axis ( Fig.…”
Section: Spontaneous Slow Waves Stereotypically Propagate Along Certainsupporting
confidence: 88%
See 1 more Smart Citation
“…The propagation speed in source space ranged from 0.4 to 6.3 m/s. The average speed was Ϸ2.2 m/s, was remarkably consistent across subjects (ranging from 2.0 to 2.3 m/s), and was roughly in agreement with previous estimations from EEG and computer simulations (9,23). Visual inspection of the streamlines for the spontaneous slow waves for each subject suggested the existence of a mesial slow wave highway oriented along the anterior-posterior axis ( Fig.…”
Section: Spontaneous Slow Waves Stereotypically Propagate Along Certainsupporting
confidence: 88%
“…Unit recording studies also support this interpretation (34). While cortical currents are typically thought to arise from the summation of inhibitory and excitatory postsynaptic potentials from the local neural population (13), synaptic input is greatly reduced during the downstate (23,(35)(36)(37). This suggests that postsynaptic potentials are not entirely responsible for the large currents recorded during a slow wave.…”
Section: Source Modeling Hd-eeg Is Uniquely Suited To Studying Indivimentioning
confidence: 99%
“…However, because the available combination of the neuron and synapse models do not exactly match those used in the Flysim simulator, we tested NEST with two sets of combinations, with one requiring more and the other requiring less computational power than our simulator. We first tested the HT model (Hill and Tononi 2005) in NEST because this model offers a synaptic dynamic that is comparable to that used in Flysim. However, the HT model is endowed with soma dynamics that are more complex than ours.…”
Section: Simulator Benchmarkmentioning
confidence: 99%
“…Hill and Tononi [6] have carried out simulations with a more comprehensive thalamocortical network that show the importance of cortical-cortical interactions in establishing and maintaining the oscillation. Experimental work on the cortical nature of the slow oscillation includes that of Steriade et al [7], who demonstrated that the slow oscillation is maintained in cat cortex following lesioning of the thalamus.…”
mentioning
confidence: 99%
“…The depolarized "up" and hyperpolarized "down" states are viewed as stable solutions for the mean membrane potential, with the down-to-up transitions being driven possibly by spontaneous neurotransmitter release [12] or random summation of EPSPs [13], and the up-to-down transition driven possibly by voltage-gated ionic (e.g., K + ) currents [5,6,14], or changes in synaptic weight [6,15]. Molaee-Ardekani et al, using a broadly similar model, have taken a different view of the phenomenon, interpreting the small slow waves seen in light anaesthesia as small, unstable excursions away from the equilibrium state, and the large slow waves of deep anaesthesia as limit cycles of the bulk behavior of the cortex [16].…”
mentioning
confidence: 99%